THE EFFECT OF SERVICE QUALITY, PRICE AND LOCATION ON CUSTOMER SATISFACTION AT CAFÉ HIDE COFFEE CLUB IN LHOKSEUMAWE CITY - Ajra Ahdima; T. Edyansyah; Ikramuddin; Siti Maimunah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the Influence of Service Quality, Price and Location on Customer Satisfaction at Cafe Hide Coffee Club in Lhokseumawe City. The data used in this study is primary data obtained by distributing questionnaires to 112 respondents who are customers who visit Cafe Hide Coffee Club Lhokseumawe City. The analysis tools used were multiple linear regression test and hypothesis test using t-test and f-test. The results of the study showed that partially and simultaneously the variables of Service Quality, Price and Location had a significant positive effect on customer satisfaction at Cafe Hide Coffee Club in Lhokseumawe City. For the next researcher, it is hoped that they can expand the research by considering or using other variables on customer satisfaction, such as the atmosphere of the café, product quality, facilities and so on. This research is also expected to be a source for future researchers who want to conduct research related to café customer satisfaction.